Two-sided Effect of Empowering Leadership on Follower’s Job Stress: The Mediation Effect of Self-efficacy and Felt Accountability and Moderated Mediation by Perceived Organizational Support - Kang, Yun Jin; Sohn, Young Woo (Korean Journal of Industrial and Organizational Psychology, 2020)
In this study, we aimed to investigate the two-sided effect of empowering leadership on follower’s job stress by focusing on the potential for positive and negative effects of empowering leadership. Based on the empowerment theory and the role theory of accountability, we examined the mediating effects of self-efficacy and felt accountability and the moderated mediation effects of perceived organizational support(POS) in the relationship between empowering leadership and job stress. A total of 427 Korean employees participated in this study through an online survey. The results show that empowering leadership has indirect effects on job stress mediated by self-efficacy and felt accountability. Specifically, empowering leadership reduced job stress via increased self-efficacy, while increased job stress via increased felt accountability. Evidence was also found of the moderating role of POS: the positive relation between felt accountability and job stress was stronger for those with a low level of POS than those with a high POS. However, the moderating effect of POS was not found in the relationship between self-efficacy and job stress. In addition, the mediating effect of felt accountability was moderated by POS in the relationship between empowering leadership and follower’s job stress. Based on the results, we discuss several implications, limitations, and recommendations for future research.